INVESTIGATION OF BRAKING PERFORMANCE AND THERMAL EFFECT OF SINTERING OF BRAKE PADS WITH Al2O3 ADDITIVE - Karaca, Faruk; Unal, Engin; Can, Ilhan (Vinca Inst Nuclear Sci, 2022)
Nowadays the improvement researches of pad materials, which are widely used in braking mechanisms of land vehicles, still maintain their popularity. In general, it has been proven by the studies that the material characteristics of the brake pads in composite structure vary greatly depending on the manufacturing parameters. In this study, the effects of sintering of Al2O3 added composite pads on braking performance via surface temperature were investigated. In this context, 50, 75, and 125 mu m Al2O3 particles were added to the lining composition and the results were evaluated comparatively. The braking performances of the tested samples were evaluated in terms of pad wear, pad surface temperature and friction coefficient. As a result, it was observed that the braking performance of sintered Al2O3 additives in all three dimensions was better.
Keywords: brake pad; braking performance; sintering; wear